2020
DOI: 10.1103/physreva.101.010303
|View full text |Cite
|
Sign up to set email alerts
|

Contextual bound states for qudit magic state distillation

Abstract: Identifying necessary and sufficient conditions for universal quantum computing is a long-standing open problem for which contextuality is, perhaps, the only promising solution [Howard et al. Nature 510, 351 (2014)]. To justify this conjecture, Howard et al. showed that contextuality is equivalent to Wigner negativity for qudits, and is therefore necessary and possibly sufficient for qudit magic state distillation. Here, we reformulate magic state distillation in the language of discrete phase space, to show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In [18], it was also shown that negativity of the Wigner function is equivalent to contextuality with respect to stabilizer measurements. It was also recently shown that no finite magic state distillation routine can distill states tight to the boundary of any facet of the Wigner polytope [50], generalizing a well-known result for qubits [51,52]. (See also [53,19,49,54] for related work.…”
Section: Discrete Wigner Functionsmentioning
confidence: 59%
“…In [18], it was also shown that negativity of the Wigner function is equivalent to contextuality with respect to stabilizer measurements. It was also recently shown that no finite magic state distillation routine can distill states tight to the boundary of any facet of the Wigner polytope [50], generalizing a well-known result for qubits [51,52]. (See also [53,19,49,54] for related work.…”
Section: Discrete Wigner Functionsmentioning
confidence: 59%
“…has a threshold to depolarizing noise of 3/4. While it can be shown that no magic state distillation routine based on a finite stabilizer code can achieve this threshold [14,47], the possibility remains that a sequence of stabilizer codes exist that distil the strange state, whose threshold approaches 3/4. Of course, the ternary Golay code is an extremely special error-correcting code, and there is no reason to expect that one can generalize it to obtain such a sequence of codes.…”
Section: Discussionmentioning
confidence: 99%
“…We use the algorithm of [14], reviewed in §2, to simulate both projection onto the stabilizer code and subsequent decoding. d out Figure 4.…”
Section: Distilling the Strange Statementioning
confidence: 99%
See 2 more Smart Citations